NARROWING THE ROLE OF WOMEN TERRORISTS IN INDONESIAN MEDIA COVERAGE - Prayona, Baiq Arwindy; Wahyudi, Gemuh Surya (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
Dian Yuli Novi is the first Indonesian women to be directly involved in an act of terrorism. However, a number of Indonesian media coverage if this case actually dwarfed Dian Yuli Novi’s role as the main perpetrator of terrorism. This paper aims to identify a number of framings found in Dian Yuli Novi’s terrorism reporting. Furthermore, this paper finds that the euphoria of number of media in exploiting this news actually makes the into symbiosis mutualism, and indirectly provides publicity for terrorist group network in Indonesia.